Pattern of Eye Diseases in an Air Force Hospital in Nigeria - Oluyinka J. Samuel, Olukorede O. Adenuga (Pakistan Journal of Ophthalmology, 2018)
Purpose: The aim of the study was to determine the pattern of eye diseases among armed forces personnel and other patients attending the eye clinic of the 347 Nigeria Air Force Hospital, Jos and to make recommendations to the hospital management for improvements in the clinic in respect of manpower and equipments. Material and Methods: A prospective study involving all new cases presenting to the eye clinic of the 347 Nigeria Air Force hospital, Jos over a 42 month period from October 2008 to March 2012. Results: A total of 1865 patients were seen during the study period with a male to female ratio of 1:1.2. The mean age was 30.46 years (SD 18.3). Majority of those seen were civilians (59%) with armed forces personnel accounting for 13%. The commonest eye diseases were allergic conjunctivitis (42%), refractive errors and presbyopia (33%) and degenerative conjuctival diseases (5%). Among armed forces personnel, refractive error and presbyopia was the commonest disorder (43%). Conclusion: The pattern of eye diseases observed in the armed forces personnel was similar to the civilian population. The eye clinic will require additional manpower and an optical laboratory is recommended to address the spectacle needs of patients with refractive errors.